Pedagogical and disciplinary issues facing the changes arising from the militarization occurred in a School Institution of the city of Alto Alegre, State of Roraima (RR), Brazil (Research, Society and Development, 2025)
This research aimed to analyze pedagogical and disciplinary issues in light of the changes resulting from militarization in a school in the municipality of Alto Alegre, Rio Grande do Norte, Brazil. It aimed to answer the following question: Does the militarization process currently being implemented in state schools in the municipality of Alto Alegre, Rio Grande do Norte, affect pedagogical and disciplinary issues in schools? This study is justified by its importance, as the militarization process in Roraima is still ongoing. Initially, only four schools were militarized, but there are currently eighteen militarized schools. It also aims to reflect on how it has been implemented, what aspects and, it has been developed, the main contributions and their influences both process, the organization of the school environment, and the teacher's performance. This is a qualitative and quantitative study using the hermeneutic method and content analysis. The target population consisted of 46 teachers and 783 regular elementary and high school students, and the sample consisted of 30 teachers and 100 students. The school was randomly selected. As a result, it is clear that militarization significantly improved discipline, reduced violence, the teaching and learning process, and the quality of education. Although it is the role of the state, militarization has yielded fundamental results in schools, without detracting from the role of teachers and their fundamental role in the teaching and learning process.